Resonance: memory and emotion - Shelby, Mariah, author; Bates, Haley, advisor; Brenner, Rachel, committee member; Dineen, Mark, committee member; Plastini, Johnny, committee member (Colorado State University. Libraries, 2022)
Through an investigation into the trauma responses of my body, from dissociation to panic attacks, I have built a body of work that relies on the associations and interactions of material and process. I have developed a sensitivity to material and processes guided by the desire to communicate feelings and emotions that are difficult to put into words. These materials vary based on clinical properties, historical contexts, or personal memory. While working, I am concerned about what materials may communicate beyond their intended purpose, pushing the material to broaden my conceptual ideas.